IoT based smart street lighting system - Balakrishnan, Shivani; Kalidassen, Darshan; Manimaran, Maniggandan; Sivakumar, Shweta; Vishnu, Darshanasri (Universiti Teknologi MARA, Kedah, 2023)
Automation, power consumption, and cost effectiveness are the primary factors in the current field of technology. Automation uses clever systems to reduce the need for human labour. Since the supply of electricity is dwindling for a variety of reasons, power conservation is always a priority. We are employing IoT devices to combat these effects because, as we are all aware, energy usage has been rising daily. This research suggests a method for adjusting streetlight illumination with sensors while utilising the least amount of electrical energy possible. When a presence is detected at night, all nearby streetlights turn on to their brightest setting; otherwise, they go into standby mode. The use of LED lights is required because they outperform traditional incandescent lamps in every way. As a result, there will be a decrease in carbon dioxide emissions, power usage, maintenance and replacement expenses, and heat emissions. A real time prototyping internet of things demonstration with costs and implementation steps has been constructed to show the real-time updates of street processing and alerting the changes occur.